2014
DOI: 10.1680/bbn.13.00024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of paddlefish (Polyodon spathula) rostrum stellate bones

Abstract: The electrosensory capabilities of the rostrum of the paddlefish (Polyodon spathula) were investigated previously. However, the structure–property relationship associated with the rostrum has yet to be explored. In this study, the stellate bone properties of the rostrum are examined as a function of spatial location on the rostrum using nanoindentation and Fourier transform infrared spectroscopy. Nanoindentation results indicated a constant elastic modulus along the middle section of the rostrum. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Natural biocomposite materials such as nacre [1][2][3], bone [4,5], horn [5,6], and mineralized fish scales [7][8][9][10] are comprised of inorganic/organic nanocomposites with excellent mechanical properties, which have been inspirations for the development of man-made nanocomposites. Specifically, the nacre design is a nanocomposite with a brick and mortar morphology composed of aragonite nanoscale constituent tablets measuring approximately eight microns in length and width, 500 nm in thickness [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Natural biocomposite materials such as nacre [1][2][3], bone [4,5], horn [5,6], and mineralized fish scales [7][8][9][10] are comprised of inorganic/organic nanocomposites with excellent mechanical properties, which have been inspirations for the development of man-made nanocomposites. Specifically, the nacre design is a nanocomposite with a brick and mortar morphology composed of aragonite nanoscale constituent tablets measuring approximately eight microns in length and width, 500 nm in thickness [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…There is a fourth category in the actual rostrum that has jelly type behavior but it was not included in this part of the study. These different components of the rostrum were also experimentally identified after performing nanoindentation and tension/compression tests on the main bones and cartilages (Allison et al 2013b;Deang et al 2017). In Allison et al (2013b) through nanoindentation was found that the middle bone (hard cartilage)'s average elastic modulus measured was 12.06 GPa.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Nano-indentation experiments carried out on the rostrum revealed the material properties of the components of the rostrum [49]. The three parts of the rostrum, as shown in Figure 11, have considerably different material properties [50].…”
Section: Materials Propertiesmentioning
confidence: 99%